Uses and abuses of User-Centered Design: literature review and proposal of a tool for evaluating ethics in the design of mobile applications. Issue 1 (2nd January 2023) - Palomar-Garcia, Clara; Fernández-Planells, Ariadna; Sora-Domenjó, Carles
ABSTRACT: The aim of this paper is to study the implications and ethical variables of User-Centered Design (UCD) methods in the design of mobile applications. We carried out a review of the literature on ethics in User-Centered Design within the field of mobile applications. We studied three disciplines that are applied in the design of mobile applications and that include UCD in their definition: Human–Computer Interaction, User Experience, and Design for Behavior Change. The analysis has allowed us, firstly, to identify different ethical approaches to applying UCD, and secondly, to propose a new tool for analyzing the ethical implications of UCD taking into account two variables: alignment with the user's interests and will, and the type of influence the design generates. This paper shows that UCD methods are not always used for the benefit of the user, and asserts the ethical responsibility of design processes involving how users interact with mobile technologies as well as the importance of media education so that citizens become technologically responsible.